THE THEORY OF GENERATIONS AS A TOOL FOR BETTER UNDERSTANDING AND TEACHING MODERN SCHOOLCHILDREN - Zarina Albinovna, Alieva (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study explores the behavioral characteristics, lifestyle patterns, and value formation of Generations Z, Alpha, and Beta, focusing on their impact on education and future life paths. Methods: Through a comprehensive analysis of relevant data, the key features of these generational groups were identified, emphasizing their unique traits in learning environments and broader societal contexts. Results: The study highlights the distinct modern skills and competencies exhibited by schoolchildren from Generations Z, Alpha, and Beta, reflecting their adaptability to technological advancements and evolving societal demands. Novelty: This research offers fresh insights into generational dynamics, providing a detailed understanding of how these young generations develop values and acquire competencies crucial for success in the contemporary world.